2011
DOI: 10.1177/000348941112000707
|View full text |Cite
|
Sign up to set email alerts
|

Are Postural Restrictions Necessary for Management of Posterior Canal Benign Paroxysmal Positional Vertigo?

Abstract: In our experience, postural restrictions do not enhance the beneficial effect of the CRMs. They do not seem to have any protective role and therefore should not be recommended as an adjunct to the treatment of PSC BPPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…The results of our study are not surprising, as they are more or less in accordance with the current literature. Our findings agree with most of the previous studies (DeBoodt, 2003;Radtke et al, 2004;Roberts et al, 2005;Fyrmpas et al, 2009;De Stefano et al, 2011;Papacharalampous et al, 2012;Toupet et al, 2012) that investigated the efficacy of postural restrictions on the success rate of CRM and reported that these restrictions do not influence resolution of BPPV. In addition, most of the patients in the restricted groups expressed a serious sense of discomfort.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of our study are not surprising, as they are more or less in accordance with the current literature. Our findings agree with most of the previous studies (DeBoodt, 2003;Radtke et al, 2004;Roberts et al, 2005;Fyrmpas et al, 2009;De Stefano et al, 2011;Papacharalampous et al, 2012;Toupet et al, 2012) that investigated the efficacy of postural restrictions on the success rate of CRM and reported that these restrictions do not influence resolution of BPPV. In addition, most of the patients in the restricted groups expressed a serious sense of discomfort.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, there are contradictory reviews on the need for involvement of postmaneuver restrictions as a part of the treatment protocol for BPPV (Fyrmpas et al, 2009;De Stefano et al, 2011;Papacharalampous et al, 2012), which are used in an effort to prevent the otoconial debris from returning to the semicircular canals after treatment. Cakır et al (2006) and McGinnis et al (2009) stated positive outcomes for these restrictions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on their efficacy are contradictory [10, 14–17]. Several studies had methodological limitations: not randomized [16] or vertigo only evaluated by interrogation [14, 15, 17].…”
Section: Discussionmentioning
confidence: 99%
“…28 We found that postural restrictions do not enhance the beneficial effects of physical treatment with manoeuvres. 29 There is no statistical evidence that restrictions have any role in preventing recurrences, but they often cause neck stiffness, so for these reasons, we do not recommend any restriction to our patients.…”
Section: Final Consideration On Treatmentmentioning
confidence: 89%